2011
DOI: 10.1016/j.sdentj.2011.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Distance between implants has a potential impact of crestal bone resorption

Abstract: Adjacent implants inserted with a distance lower and higher than 1.8 mm have difference in crestal bone resorption but this difference is not statistically significant in a short period follow up. This could due to the specific implant used that has a reverse conical neck. No statistical difference was detected between implant subtypes. Post-extractive implant insertion is the major determinant in terms of peri-implant bone resorption in a short period follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Previous studies have indicated that the distance between implants and the crestal bone resorption are interdependent (Danza et al. ). Furthermore, because of the peri‐implant bone resorption that occurs when an implant is exposed to the oral environment, it has been recommended to maintain 1.5 mm between the tooth and implant to preserve the bone adjacent to the teeth (Vela et al.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that the distance between implants and the crestal bone resorption are interdependent (Danza et al. ). Furthermore, because of the peri‐implant bone resorption that occurs when an implant is exposed to the oral environment, it has been recommended to maintain 1.5 mm between the tooth and implant to preserve the bone adjacent to the teeth (Vela et al.…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of the results obtained from other studies and/or reported by the most recent literature reviews indicates that despite a large number of possible complications associated with orthognathic surgery procedures, the vast majority of them do not affect aesthetic and functional results [21,49]. Literature data suggests how these complications can be solved thanks to the joint work of surgeons, orthodontists, and operational teams [50][51][52][53][54][55][56]. The analysis of the literature and our clinical experience also led to evidence that the piezoelectric device might provide an innovative safe and effective technique compared to other rotating instruments due to the absence of macrovibrations; moreover, it is easy to be used and may provide safer control and cutting, especially in complex anatomical areas [8,11].…”
Section: Discussionmentioning
confidence: 99%
“…These measures ensure an appropriate emergence profile and facilitate acquisitions of interproximal spaces adequate for good oral hygiene. 17 Another very important aspect of postextraction implantology is in proper preparation and placement of the temporary prosthesis. The immediate prosthesis allowing immediate loading that is one of the fundamental factors for maintaining length and width of bone crest.…”
Section: Discussionmentioning
confidence: 99%